The Effectiveness Of Using Mind Mapping To Students’ English Reading Comprehension Achievement Of Analytical Exposition Text At MAS YP. Haji Datuk Abdullah In Academic Year 2021-202 - Fauziah, H Asnawi (Cybernetics: Journal Educational Research and Social Studies, 2022)
The objective of the research was to find out whether there is any significant effect of using mind mapping technique on students’ achievement in reading comprehension. The type of research was quantitative research and it was conducted by using experimental design with two classes, in experimental class consisted to 30 students and control class consisted to 30 students. In technique of collecting data, the researcher conducted pre-test, treatment and post-test by giving reading comprehension test which consist of 10 multiple choice items for each test. The result of this research show that there was a significant effect of using partner reading strategy. It can be seen from the difference between student’s mean score of pre-test and post-test in experimental class which improve from 48 to 73. The mean score of post-test control class was 52 while, the mean post-test in experimental class was 73 was higher than control class. It means, mind mapping technique can be applied to improve students’ reading comprehension.